Academic Testing Accommodations for ADHD: Do They Help? - Pritchard, Alison Esposito (Learn Disabil (Pittsbg), 2016)
This study investigated the effectiveness of five commonly administered academic testing accommodations on reading and math performance in children with attention deficit hyperactivity disorder (ADHD). A total of 96 parents of 3(rd)–8(th) grade students with ADHD participated. More than half of the sample also had parent-reported learning difficulties in reading and/or math. Individually administered cognitive and achievement test scores, types of testing accommodations received, and Maryland School Assessment (MSA) reading and math scores were obtained from these students’ school records. Taking into account grade level and co-occurring learning difficulties, none of the five accommodations investigated were associated with better MSA scores among students with ADHD who received the accommodations versus comparable students who did not. Additionally, individual variation in processing speed performance did not moderate the association between receipt of accommodations and reading or math performance. Common testing accommodations, as presently administered, may offer little benefit for students with ADHD, regardless of co-occurring learning difficulties.